Polish folk dances = Polskie tance ludowe [bladmuziek] - Lukaszewicz, Irena; Glinski, Tomasz (London : Maxwell, Love and Co., 1937)
Bibliotheek Camille Huysmans
Losbladig in map
Pools
Engels
Partituur
Keywords: volksliederen; volksdansen; Polen